Combustion Of Volatile Organic Compound VOC Pollutants In Air Stream Over ZSM-5 Supported Bimetallic Catalysts. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2004)
The pcrformance of ZSM-5 supported bimetallic catalysts with chromium as the base metal in the combustion of ethyl acetate (EAc) and benzene (Bz) is reported.